2013
DOI: 10.1590/s0102-05362013000200012
|View full text |Cite
|
Sign up to set email alerts
|

Fresh cut yam stored under different temperatures

Abstract: The objective of this study was to evaluate the microbiological, physiological and qualitative changes in fresh cut yam (Dioscorea alata) stored at different temperatures. The experimental design was completely randomized in factorial scheme 4x4, with four storage temperatures (5, 10, 15 and 20ºC) and four evaluation periods (0, 3, 6 and 9 days after processing) with four replications. The microbiological analyzes were performed at 0, 3 and 9 days after processing. Fresh cut yam stored at 5ºC kept respiration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 7 publications
2
8
0
1
Order By: Relevance
“…We found that even considering the loss of fresh weight, storing yam at 5°C did not result in diminished quality as the starch deposition on the surface prevented the slices from drying-out. Donegá et al (2013) observed similar results, however, PVC was used as packing material, which has lower thickness than our multilayer nylon packages and could have had influence on the findings.…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…We found that even considering the loss of fresh weight, storing yam at 5°C did not result in diminished quality as the starch deposition on the surface prevented the slices from drying-out. Donegá et al (2013) observed similar results, however, PVC was used as packing material, which has lower thickness than our multilayer nylon packages and could have had influence on the findings.…”
Section: Resultssupporting
confidence: 73%
“…Fresh weight loss of yam kept at 5°C did not exceed 0.08%, which was well below the results observed by Donegá et al (2013) who found a loss of 0.8%, in minimally processed yam packed in a polyvinyl chloride (PVC) film under the same temperature. We found that even considering the loss of fresh weight, storing yam at 5°C did not result in diminished quality as the starch deposition on the surface prevented the slices from drying-out.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…Such tissue damage can be reduced by using cold chain in the processing where temperature is one of the most influencing factors, in the maintenance of quality of minimally processed products (Donegá et al, 2013;Fagundes et al, 2013). The use of cold chain is required in all procedures, since all physical alterations cause a cellular injury by activating oxidative enzymes, generating browning, tissue degradation and sensory changes (Artés, 2004), which vary according to temperature.…”
Section: Introductionmentioning
confidence: 99%